A 10 year survey of acaricide residues in beeswax analysed in Italy. Issue 7 (27th October 2015) - Boi, Michela; Serra, Giorgia; Colombo, Roberto; Lodesani, Marco; Massi, Sergio; Costa, Cecilia
Abstract: BACKGROUND: The aim of this work was to provide an overview of the prevalence and level of acaricides in beeswax used in Italy in the past 10 years by analysing 1319 beeswax samples processed by the certified laboratory of the Italian Bee Research Institute. RESULTS: The proportion of samples positive to at least one active ingredient decreased between 2005 and 2009 (from 69 to 32%) and then increased again between 2009 and 2014 (from 32 to 91%). This trend is in agreement with reports from beekeepers that the use of synthetic acaricides decreased in the second half of the past decade and increased after the beginning of the colony losses phenomenon. The active ingredient with the greatest overall proportion of positive samples was coumaphos (49%), followed by fluvalinate (38%) and chlorphenvinphos (25%). The indicator for amitraz, 2, 4‐dimethylphenylformamide (DMPF), was detected in a very small proportion of samples (6%), while residues of cymiazole were never found. CONCLUSIONS: In more than half of the analysed samples, residues of at least one active ingredient were detected. The mean levels of residues of all the considered active ingredients in the positive samples may represent a source of accumulation in beeswax and pose risks to honey bee health. © 2015 Society of Chemical Industry